На академічних перспективах - Ковалів, Ю. (Слово і Час, 2018)
У статті розкрито генетичні основи сучасного академічного літературознавства, репрезентованого
Інститутом літератури ім. Т. Г. Шевченка НАН України, складні шляхи його еволюції в першій
половині ХХ ст. The paper discovers origin of modern academic literature studies represented by T. Shevchenko
Institute of Literature of the National Academy of Sciences of Ukraine, and complicated ways of its
evolution in the 1st half of the 20th century. It adjusts assertions about the Institute’s genesis made in
the publication “T. Shevchenko Institute of Literature of the National Academy of Sciences of Ukraine,
1926–2001: Pages of History” (2003). It was stated in the book that the modern Institute of Literature,
which was actually established in 1937, is connected to establishment of Taras Shevchenko Institute
(1926), while the authors also referred to VUAN. In fact, the origin of the modern Institute of Literature
is rooted in UAN (Ukrainian Academy of Sciences, afterwards VUAN) which was officially established
by the act of the hetman P. Skoropadskyi (14 November 1918) and which, adopting the experience
of Shevchenko Scientific Society and other scientific and scholarly organizations, paved the future
ways of modern literature studies.
Creative relationship was then established between VUAN and Taras Shevchenko Institute, despite
the destructive intervention of the outside non-scholarly forces (Communist party) in the 1920s, and
ideas of essential literature studies were exchanged. It often happened that the same researchers
were employed by both institutions, they discovered and resolved the same problems, developed
important sectors of medieval studies, new and modern literature, theory of literature, comparative
studies, poetry studies, Shevchenko studies, Slavic studies, foreign literature, Oriental studies, folklore
studies, formed the basis of Franko studies, Lesia Ukrayinka studies, textual studies etc.
This year Ukraine celebrates the 100th anniversary of establishing the UAN, that requires an
adequate reconsideration of succession in literature studies discourse in historical perspective. There
is a need in researching interruptions in this dynamics and revealing their reasons. The integrity of
national philological culture should be considered in its diversity, in its synchronic and diachronic
relations. That is why the time frame must necessarily be extended from 1926 to 1918 in the past
and reach the present day.